Models of voltage and current impulse generator and low voltage multilayer varistor - Quyen, Huy Ánh; Tran, Tùng Giang; Le, Quang Trung (Journal of Technical Education Science, 2010)
This paper presents the model of voltage and current impulse generator 6kV 1.2/50µs, 3kA 8/20µs, according to the international standard IEEE C62.41 and the model of low voltage multilayer varistor (MLV) that have the necessary complexity and high accuracy. The model of impulse generator is used for simulation, evaluation, inspection of the response of low voltage MLV model with lighting standard impulses. The model of low voltage MLV has the parameters such as nominal surge current, let-through voltage and the quantity of shunt connected MLV. The method to determine the number of lighting impulses that the MLV can respond is also presented.